Genome sequences and annotation of two urinary isolates of E. coli. Issue 1 (December 2016) - Price, Travis; Mehrtash, Arya; Kalesinskas, Laurynas; Malki, Kema; Hilt, Evann; Putonti, Catherine; Wolfe, Alan
Abstract The genusEscherichia includes pathogens and commensals. Bladder infections (cystitis) result most often from colonization of the bladder by uropathogenicE. coli strains. In contrast, a poorly defined condition called asymptomatic bacteriuria results from colonization of the bladder withE. coli strains without symptoms. As part of an on-going attempt to identify and characterize the newly discovered female urinary microbiota, we report the genome sequences and annotation of two urinary isolates ofE. coli : one (E78) was isolated from a female patient who self-reported cystitis; the other (E75) was isolated from a female patient who reported that she did not have symptoms of cystitis. Whereas strain E75 is most closely related to an avian extraintestinal pathogen, strain E78 is a member of a clade that includes extraintestinal strains often found in the human bladder. Both genomes are uncommonly rich in prophages.